2011
DOI: 10.1002/hed.21437
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Sonic hedgehog pathway in squamous cell carcinoma of the skin and the mucosa of the head and neck

Abstract: Hedgehog signaling is differentially regulated in squamous cell carcinomas of the skin and the head and neck. Sonic hedgehog expression may serve as a prognostic factor in patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 31 publications
3
43
2
2
Order By: Relevance
“…Schneider et al [22] failed to note any expression of SHH signaling proteins in oral normal mucosa. However, in our study, low levels of GLI-1 were expressed in NNT1.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Schneider et al [22] failed to note any expression of SHH signaling proteins in oral normal mucosa. However, in our study, low levels of GLI-1 were expressed in NNT1.…”
Section: Discussionmentioning
confidence: 98%
“…Schneider et al [22] assessed the expression of SHH signaling proteins in head and neck squamous cell carcinomas. Here, we found the transcriptional levels of genes in the SHH pathway in human OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an important role of the Hh signaling pathway in the development of a variety of solid tumors and have revealed its impact on the outcome of most incurable aggressive malignancies [Watkins et al 2003;Liao et al 2009;Watkins and Peacock, 2004;Datta and Datta, 2006;Brunner et al 2010;Schneider et al 2011;Vestergaard et al 2006]. The Hh signaling pathway plays a crucial role in tumorigenesis when reactivated in adult tissues through sporadic mutations and other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schneider et al [28] published data on the expression of the HH pathway in squamous cell carcinomas of the skin in comparison to HNSCC; however, they used only semiquantitative methods for analysis and found heterogeneous expression rates in these tumour entities. Wang et al [29] only considered SHH, PTCH, and Gli1 expression in oral squamous cell carcinomas from 40 patients, but found that PTCH overexpression was associated with lymphatic spread and that Gli1 overexpression was correlated with primary tumour size, lymphatic metastasis and tumour recurrence (fig.…”
Section: Discussionmentioning
confidence: 99%